The influence of the number of free surfaces on the energy distribution and attenuation law of blasting vibration signals from peripheral holes: field experiment and simulation - Lan, Riyan; Wang, Zhen; Lu, Jianyou; Zhou, Zilong; Chen, Lu; Gao, Shan (Frontiers in Earth Science, 2023)
Blasting vibration is directly related to structural damage. A detailed understanding of the characteristics and propagation laws of blasting induced vibration velocity and frequency is a prerequisite for conducting vibration intensity safety evaluation, and is of great significance for reasonable and efficient blasting parameter design and vibration control. Millisecond delay blasting is used to excavate the tunnel, and rock mass is significantly affected by vibration caused by surrounding holes. In order to study the influence of the number of free surfaces on the energy distribution and attenuation of blasting vibration signals from peripheral holes, field tests and numerical simulation tests were conducted in the same tunnel. The research results show that under the same blasting parameters and propagation media, the particle peak vibration velocity of peripheral hole blasting with a free surface number of 1 is greater than the particle peak vibration velocity of peripheral hole blasting with a free surface number of 2. The longitudinal Fourier main frequency caused by peripheral hole blasting decreases with distance from the monitoring point under different numbers of free surfaces. Moreover, its centroid frequency and zero crossing frequency also exhibit attenuation patterns. In the same distance from the explosion source, the fewer free surfaces, the lower the centroid frequency and zero crossing frequency. Therefore, from the perspective of blasting induced vibration, the smaller the number of free surfaces, the greater the damage caused by peripheral hole blasting to the structure at a distance of about 20 meters. Furthermore, two free surface peripheral holes blasting results in a higher high frequency energy ratio than one free surface peripheral hole blasting. In addition, Numerical simulations show that rock fragmentation increases with the number of free surfaces of rock after blasting.